Dreams, visions, and spiritual authority in Merovingian Gaul - Moreira, Isabel (Cornell University Press, 2000)
"In early medieval Europe, dreams and visions were believed to reveal divine information about Christian life and the hereafter. No consensus existed, however, as to whether all Christians, or only a spiritual elite, were entitled to have a relationship of this sort with the supernatural. Drawing on a rich variety of sources - histories, hagiographies, ascetic literature, and records of dreams at saints' shrines - Isabel Moreira provides insight into a society struggling to understand and negotiate its religious visions."--Jacket